Evaluating maize (Zea mays L.) management practices implementing sensitivity analysis of vegetation indices - Flynn, K. Colton; Smith, Douglas R.; Lee, Trey O.; Laguer-Martinez, Doris; Ma, Shengfang; Zhou, Yuting (Soil & tillage research, 2024)
Conservation agriculture and sustainable agronomic principles include several management practices such as cover cropping, no-till, and alternative fertilization rates. Each of these practices can result in changes among agricultural productivity, sustainability for future farming, and protections for the environment. These management practices are important concepts that can be applied in the production of maize (Zea mays L., corn). The aim of this three-year study (2018–2020) was to compare maize health across two fields located in Riesel, TX under varying management approaches and precipitation conditions. The first field utilized ‘business as usual’ operations characterized by the implementation of tillage, fertilization at a maximum rate (10.06 Mg/ha), and no cover crops. The second field utilized ‘aspirational’ cultivation techniques categorized by no tillage, cover crops, and an alternative method for rate of fertilization. Each field was subject to satellite-based remote sensing methods incorporating Normalized Difference Vegetation Index (NDVI), Enhanced Vegetation Index (EVI), and Normalized Difference Red Edge (NDRE). Indices were subject to sensitivity analyses to determine the most sensitive index for maize under various managements and precipitation conditions. The most sensitive index (EVI) served as a proxy for time series analysis for maize health under the varying managements and rainfall conditions. The results suggest improvements to maize health are experienced over time when aspirational managements are employed, even though business as usual management resulted in higher yields. However, studies with greater duration could point to these perceived benefits over a long-term implementation. Nevertheless, productivity comparisons considering amount of input (i.e. fertilizer) suggests an increase in efficiency each year for the aspirational management. These findings suggest factors such as improved soil health from implementation of no-till and cover crops contribute to field health, efficiencies, and resiliency across varying precipitation conditions. •Enhanced vegetation index (EVI) served as the most sensitive proxy for maize health.•Sensitivity of health proxies were consistent across varying climates and managements.•Increasing pattern of maize health/yield were recognized in conservation practices.•Conservation practices improved long-term resiliency of food production.